The Existence of Fraction Domino Learning Media on the Mathematical Communication Skills of Elementary School Students - 'Arif, Muhammad; Wandini, Rora Rizky (Yayasan Sembilan Pemuda Indonesia, 2025)
The purpose of this study was to examine the effect of fractional domino learning media on the mathematical communication skills of second-grade elementary school students. This study employed a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The experimental group received the treatment, while the control group did not. The sample consisted of 58 second-grade students from MIN 4 Kota. Two data collection techniques were used in this study: observation and a mathematical communication ability test. Data analysis was conducted using descriptive statistics, followed by normality and homogeneity tests, and hypothesis testing using independent sample t-tests. The results indicated that fractional domino learning media positively affected students’ mathematical communication abilities, as evidenced by the average post-test score of 14.66 for the experimental group and 11.31 for the control group. The hypothesis test yielded a sig. (2-tailed) value of 0.001, which was smaller than the α level of 0.05, indicating a significant difference in post-test scores between the experimental and control groups. Based on these findings, it can be concluded that the use of fractional dominoes enhances the mathematical communication skills of second-grade elementary school students.